Search strategies in human visual inspection - Charles, Rebecca; Tailor, Mitul; Fletcher, Sarah R. (Taylor and Francis, 2015)
Visual inspection in high value manufacturing is a task currently undertaken by highly trained human operators. Human operators show variability in detection rates and strategies. Work has been carried out (within the centre?) to automate certain aspects of visual inspection using robots. This paper presents the results of a small study investigating human visual search patterns and their effect on defect detection rates. This paper will focus on the human aspect of visual search which can provide an insight into the most effective ways of detecting defects.